Development A Simple Model for Preliminary Evaluation on Extreme Rainfall Induces Shallow Slope Failure - Agus Setyo Muntohar, Jazaul Ikhsan (Quality in Research, 2013)
A simple method is developed in this paper to evaluate rainfall induces slope instability. The method dealt with one dimensional infiltration on the shallow slope. The study was focused on the study of the effect of rainfall pattern, duration, soils type and slope angle on the stability of slope. Two soil types, those were low and high permeability, and slope angle were selected to examine the proposed model. The results of the study show that the proposed model was simple model and suitable to assess rainfall induced slope instability especially shallow landslides type. The proposed model enable to estimate the infiltration and slope stability during the rainfall as the FEM results was more conservative. Infiltration was strongly affected by rainfall pattern, inclination of slope and the hydraulic properties of soil.